Situation Report: Romania, 26 October 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A New Twist to Personnel Changes? Party and Government Reshuffle Ceausescu Descends on Bucharest Food Markets Romanian-American Exchange of Views on Human Rights Continues US Assistant Secretary of Defense Frank Carlucci Visits Romania Economic Relations with Greece Synthetic Diamond Production Copper Mining and Refining Rice Paddies and Cotton Plantations in Romania? Student Help with Harvesting Proves Unsatisfactory